A new species and new record of Nemourinae (Plecoptera: Nemouridae) from China - Li, Mengyu; Yang, Ding; Li, Weihai; Mo, Raorao (Zootaxa, 2024)
A new species of the genus Illiesonemoura Baumann, 1975, I. lulang sp. nov., is described from Xizang, southwestern China, and compared with a related congener. Zapada quadribranchiata (Zhiltzova, 1977) is recorded from China for the first time.